Impairment of executive functions in patients with Generalized Anxiety Disorder (Research, Society and Development, 2022)
Generalized Anxiety Disorder (GAD) affects individuals of all ages, causing physical and cognitive impairment, thus reducing their quality of life. The evaluation of the cognitive capacity of patients with GAD is an important tool when trying to understand the damages that this disorder brings to the individual. Therefore, the present study aimed to understand if there are losses or alterations in cognitive functions, mainly executive ones of these individuals. Twenty-one subjects, both men and women, underwent a 2-back test to assess working memory performance and a Stroop Task to assess inhibitory control, comprising a TAG Group (n = 11) and a Control Group (n = 10). The patients were selected from ambulatory care at a tertiary hospital in the Western São Paulo. The results showed important differences in the performance of patients with GAD, who exhibited equivalent reaction time (RT) performance in the 2-back test, but with a greater number of errors. At the Stroop task they are consistently slower than the Control Group, for the equivalent number of errors. Taken together, these data point to significant prejudice in GAD, even within a limited sample of subjects.